Pengaruh Lingkungan Kerja, Komunikasi, Loyalitas Kerja Terhadap Kinerja Karyawan PT. Bima Sakti Medika Palembang - Meisya Ana Pratami; Fauziah Afriyani; Muhammad Bahrul Ulum (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of the work environment, communication and work loyalty on employee performance at the PT Bima Sakti Medica Palembang office. The selected sample was 76 respondents. This research data was obtained from a questionnaire (primary data). Analytical techniques used in this research is the multiple linear regression method. Results Data analysis with the help of SPSS 27 shows that the results of the hypothesis test partially (t-test) Work Environment has a posotive and significant effect on the system Employee performance. Communication has a positive and significant effect on employee performance. And work loyalty has apositive and significant effect on the employee performance system. Meanwhile, the results of the simultaneous test (f-test) based on the termination coefficient value prove that the Work Environment, Communication and Work Loyalty variables together have a positive and significant effect on Employee Performance.